Shape Control of CdTe Nanocrystals: Influence of the Solvent Composition and Ligand Effects. (6th February 2013) - Jin, Xiaoping; Parisi, Jürgen; Kolny-Olesiak, Joanna
Abstract : CdTe nanocrystals were synthesized by the hot-injection method with a mixture of oleylamine and octadecene as a solvent. The influence of the composition of the solvent and of the injection solution on the shape of CdTe nanoparticles was investigated. Various shapes of CdTe nanocrystals, such as nanodots, nanorods, multipods, and nanowires, could be obtained by changing the reaction conditions. Tuning the reactivity of both the cadmium and the tellurium precursors at the same time was found to be the main reason for the shape control of CdTe nanocrystals in this reaction system. The reactivity of the Cd precursor was controlled by the composition of the solvent, while the activity of the Te precursor could be influenced by using trioctylphosphine and tributylphosphine in the injection solution.